SECONDARY STUDENTS' ATTITUDES IN VOCABULARY LEARNING ASSISTED BY DUOLINGO - Dea Nur Aprilani; Mansyur Srisudarso; Iwan Ridwan (IKIP Siliwangi, 2023)
Vocabulary learning in second and foreign languages is needed to make effective communication, it is impossible to use a language effectively without an adequate vocabulary and also to master other skills in English. However, many high school students have poor knowledge of vocabulary mastery because the process of remembering vocabulary is considered boring and stressful. This study focused on investigating the students' attitudes toward Duolingo in vocabulary learning at one vocational high school in Bandung. This research belongs to qualitative research, the researcher collected data through semi-structured interviews with three students of tenth-grade hospitality major. Data were analyzed using thematic analysis. The results found five main themes. The findings of this study are expected to provide information for the English teacher on the student's positive attitudes toward Duolingo in vocabulary learning. It also benefits teachers, teachers can develop teaching vocabulary techniques by using this application to grab students’ attention to learn more vocabulary. Keywords: Duolingo; Students’ Attitude; Vocabulary Learning